Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b:
1: \(\Leftrightarrow2x\left(x+2\right)=0\)
=>x=0 hoặc x=-2
a: \(=\dfrac{6x^2+9x+8x+12}{2x+3}=\dfrac{3x\left(2x+3\right)+4\left(2x+3\right)}{2x+3}\)
=3x+4
b: \(=\dfrac{5x^2-2x+15x-6}{5x-2}\)
\(=\dfrac{x\left(5x-2\right)+3\left(5x-2\right)}{5x-2}=x+3\)
c: \(=\dfrac{-8x^2+20x+2x-5-10}{2x-5}=-4x+1+\dfrac{-10}{2x-5}\)
d: \(=\dfrac{14x^2-35x+2x-5}{2x-5}=\dfrac{7x\left(2x-5\right)+\left(2x-5\right)}{2x-5}\)
=7x+1
e: \(=\dfrac{2x^3+x^2+6x^2+3x+12x+6}{2x+1}\)
\(=\dfrac{x^2\left(2x+1\right)+3x\left(2x+1\right)+6\left(2x+1\right)}{2x+1}=x^2+3x+6\)
f: \(=\dfrac{x^3-2x^2+6x^2-12x+x-2}{x-2}=x^2+6x+1\)
g: \(=\dfrac{12x^3+6x^2-4x^2-2x+6x+3}{2x+1}=6x^2-2x+3\)
b: \(=x^2-9-\left(x^2+3x-10\right)\)
\(=x^2-9-x^2-3x+10=-3x+1\)
c: \(=\dfrac{2x^3-x^2+x-10x^2+5x-5}{2x^2-x+1}=x-5\)
d: \(=8x^3+27-8x^3+2=29\)
Answer:
6x^3 + 11x^2 - 12x - 9 2x + 5 6x^3 + 15x^2 3x^2 - 2x - 1 -4x^2 - 12x - 9 -4x^2 - 10x -2x - 9 -9x - 5 -4
\(6x^3+11x^2-12x-9:(2x+5)(3x^2-2x-1)-4\)